Palindromic carbazole derivatives: unveiling their antiproliferative effect via topoisomerase II catalytic inhibition and apoptosis induction - Mateusz Olszewski; Natalia Maciejewska; Anoop Kallingal; Agnieszka Chylewska; Aleksandra M. Dąbrowska; Małgorzata Biedulska; Mariusz Makowski; José M. Padrón; Maciej Baginski (Taylor & Francis Group, 2024)
AbstractHuman DNA topoisomerases are essential for crucial cellular processes, including DNA replication, transcription, chromatin condensation, and maintenance of its structure. One of the significant strategies employed in cancer treatment involves the inhibition of a specific type of topoisomerase, known as topoisomerase II (Topo II). Carbazole derivatives, recognised for their varied biological activities, have recently become a significant focus in oncological research. This study assesses the efficacy of three symmetrically substituted carbazole derivatives: 2,7-Di(2-furyl)-9H-carbazole (27a), 3,6-Di(2-furyl)-9H-carbazole (36a), and 3,6-Di(2-thienyl)-9H-carbazole (36b) - as anticancer agents. Among investigated carbazole derivatives, compound 3,6-di(2-furyl)-9H-carbazole bearing two furan moieties emerged as a novel catalytic inhibitor of Topo II. Notably, 3,6-di(2-furyl)-9H-carbazole effectively selectively inhibited the relaxation and decatenation activities of Topo IIα, with minimal effects on the IIβ isoform. These findings underscore the potential of compound 3,6-Di(2-furyl)-9H-carbazole as a promising lead candidate warranting further investigation in the realm of anticancer drug development.